2019
DOI: 10.2166/wcc.2018.006
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting extreme events: making sense of noisy climate data in support of water resources planning

Abstract: Global climate model (GCM) projections are generally considered the best source of information for predicting future climate and hydrologic conditions in the face of a changing climate. Understanding and interpreting GCM projections is therefore critical for water resources planning. Unfortunately, this can be a challenging task as climate model data, particularly precipitation data, are notoriously noisy with large scatter and lacking in apparent patterns or trends. There is also usually large projection vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The modelling results illustrated a noticeable disparity between the accuracy of the temperature modelling when compared with the rainfall modelling using factors such as coefficients of determination. Cox et al ( 2019 ) also reported a similar outcome and detailed it as intrinsically noisy, featuring a large scatter with no obvious trend. However, due to the capabilities offered by such methods (e.g., Aghelpour and Varshavian 2020 ; Nguyen et al 2019 ), the authors committed to expanding their approach and investigating the potential for improvement of GMDH.…”
Section: Introductionmentioning
confidence: 79%
“…The modelling results illustrated a noticeable disparity between the accuracy of the temperature modelling when compared with the rainfall modelling using factors such as coefficients of determination. Cox et al ( 2019 ) also reported a similar outcome and detailed it as intrinsically noisy, featuring a large scatter with no obvious trend. However, due to the capabilities offered by such methods (e.g., Aghelpour and Varshavian 2020 ; Nguyen et al 2019 ), the authors committed to expanding their approach and investigating the potential for improvement of GMDH.…”
Section: Introductionmentioning
confidence: 79%